Current status and perspectives of immune checkpoint inhibitors for colorectal cancer. (18th November 2020) - Hirano, Hidekazu; Takashima, Atsuo; Hamaguchi, Tetsuya; Shida, Dai; Kanemitsu, Yukihide
Abstract: Immunotherapy, especially immune checkpoint inhibitors, has revolutionized the standard-of-care of multiple types of tumors. For colorectal cancer, the clinical development of immune checkpoint inhibitors is mainly separated according to the status of microsatellite instability or mismatch repair in a tumor. High-level microsatellite instability/deficient mismatch repair metastatic colorectal cancer generally has a tumor microenvironment with infiltration of T cells, associated with a favorable response to immune checkpoint inhibitors. Immune checkpoint inhibitors, including pembrolizumab (anti-PD-1 inhibitor) and nivolumab (anti-PD-1 inhibitor) with or without ipilimumab (anti-CTLA-4 inhibitor), have been integrated into the standard-of-care for high-level microsatellite instability/deficient mismatch repair metastatic colorectal cancer. Conversely, limited T-cell infiltration in the tumor microenvironment of microsatellite stable/proficient mismatch repair metastatic colorectal cancer, which constitutes the majority of metastatic colorectal cancer, is assumed to be a major resistant mechanism to immune checkpoint inhibitors. Currently, clinical trials to improve the clinical activity of immune checkpoint inhibitors by immunomodulation are ongoing for metastatic colorectal cancer. Furthermore, immune checkpoint inhibitors are under development in neoadjuvant and/or adjuvant setting. Here, we review the existing clinical data with ongoing trials and discuss the future perspectives with a focus on the immunotherapy of colorectal cancer. Abstract : This review article summarized the current status and future perspectives of immunotherapy for colorectal cancer.